Room temperature operated diffraction limited λ ≃ 3 µm diode lasers with 37 mW of continuous‐wave output power. Issue 10 (1st May 2013) - Hosoda, T.; Liang, R.; Kipshidze, G.; Shterengas, L.; Belenky, G.
Abstract : Single spatial mode GaSb‐based type‐I quantum well diode lasers operating near 3 µm at room temperature were designed and fabricated by chlorine‐free dry etching technique. The etching profile was optimised to minimise the optical loss. The 5.5 µm‐wide ridge lasers demonstrated the same slope efficiency as that of 100 µm‐wide multimode devices and generated 37 mW of continuous‐wave output power at 17°C.